THE ROLE AND IMPORTANCE OF C# PROGRAMMING TOOLS IN INFORMATION SECURITY (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The C# programming language plays an important role in information security for several key reasons. C# was developed by Microsoft, and as a result, it is highly integrated with Windows operating systems. Since Windows is widely used in enterprise environments, C# is an excellent choice for developing security tools that need to interact with system processes and underlying Windows architecture. C# provides access to Windows APIs, enabling security professionals to perform system-level tasks such as process management, memory analysis, and network monitoring. C# is a powerful tool for penetration testers who simulate attacks on systems to identify vulnerabilities.